The Politics of Silence: art and education at Política do Impossível collective’s poetic - Eboli Nogueira, Pedro Caetano (Revista Brasileira de Estudos da Presença, 2022)
The paper aims to think the interweavings between art, politics and education within the action titled Traga Sua Luz, carried out in 2008 by Política do Impossível collective. Intended to question the process of gentrification in Luz neighborhood - located at São Paulo city center -, it consisted of a silent and collective performance in which candles and small lamps were carried and deposited on lands expropriated by the then mayor. Through the theoretical contributions of Walter Benjamin, Georges Didi-Huberman, Roland Barthes and Jacques Rancière, this paper elucidates how the suspension of the merely communicative function of language permeates art, education and a politics of silence.